Expert Opinion in Construction Disputes: Duties and Professional Liability of Experts - Waidhofer Ludeña, Katherine (2020)
Disputes in the construction industry usually require the participation of a variety of qualified specialists who can assist the tribunal in understanding the high complexity of contract performance. In arbitration, the expert is generally appointed by one of the parties, although his opinion is solely obliged to the tribunal. Naturally, this relationship of perceived ambivalence between the expert, the party who appoints him and the tribunal can raise questions about the impartiality and independence of his opinion.In this article, the author analyzes the international statutes and soft law that regulate the duties and professional responsibilities of experts in construction arbitration. In particular, she evaluates the treatment of the figure under Peruvian law and sheds light on whether the regulation provided by the Civil Code is sufficient. Furthermore, the author remarks the main measures adopted by arbitration tribunals to test the objectivity of expert opinions and the applicable standard of care for determining possible non-compliance by experts in the Peruvian legal system.